The Effect of Work Discipline on Employee Performance: A Study of Motivation Mediation as a Connecting Factor in The Medan City Revenue Office - Waruwu, Ahmad Aswan (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine and analyze the effect of discipline on employee performance, the influence of motivation on employee performance, and whether motivation mediates the relationship between discipline and employee performance at the North Medan City Regional Revenue Office. Using a quantitative approach, this study involved 87 permanent employees selected using purposive sampling. Data were collected through questionnaires and analyzed using path analysis with data processing using SPSS software. The results indicate that discipline has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, and motivation is a mediating variable between discipline and employee performance at the North Medan City Regional Revenue Office. These findings confirm that improved discipline impacts employee performance if accompanied by improvements in employee motivation.